Digital Conquerors: Minecraft and the Apologetics of Neoliberalism - Dooghan, Daniel (Games and Culture, 2019)
The widespread popularity of sandbox games, and Minecraft in particular, may be a recent phenomenon, but their appeal may be much older. Rather than representing a wholly new development in gaming, these games may participate in a larger media ecology that flatters a neoliberal worldview. This research calls for greater attention to the coercive economic assumptions encoded in gamemechanics. Drawing on scholarship in ludology, postcolonial studies, and phenomenology, it suggests that sandbox games like Minecraft habituate players to myths of empire and capital that rationalize political and economic inequality. More than simply offering a blank slate for player creation, Minecraft rewards players for assuming their entitlement to the world’s resources and thus their superiority over other inhabitants of the game world.
Keywords: 1-Jeux vidéo; 2-Théories et épistémologie postcoloniales et décoloniales; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); _Nettoyé